Dignified development: democratic deepening in an Indian state. Issue 1 (2nd January 2021) - Roy, Indrajit
ABSTRACT: Beyond questions of transition to and backsliding from democracy, scholars are beginning to debate the contours of democratic deepening. This paper develops an account of 'dignified development' to elaborate understandings of democratic deepening through an interpretive synthesis of the secondary literature on Bihar between 1990 and 2005 when the much-maligned Lalu Prasad Yadav controlled the State's governance. At a time when democracy is under threat not only in India but across the world, reflections on democratic depth offer us lessons on how democracy might be renewed and reinvigorated.